Total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol - Patel, Ramesh M.; N. P. Argade (Synthesis-Stuttgart, 2009)
Starting from citraconic anhydride, the first total synthesis of (+/-)-1,3,4,5-tetragalloylapiitol has been demonstrated via a stepwise route involving generation of an apiitol derivative followed by benzoylation.
Keywords: (+/-)-1; 3; 4; 5-tetragalloylapiitol; allylic hydroxylation; Natural products; osmium tetroxide

Total synthesis of proposed auranthine - Kshirsagar, Umesh A.; Puranik, Vedavati G.; N. P. Argade (Journal of Organic Chemistry, 2010)
Starting from CBz-protected glutamic anhydride and Boc-protected o-aminobenzyl amine, the first total synthesis of proposed structure of auranthine has been reported. An intramolecular aza-Wittig reaction involving a lactam carbonyl group that delivered the diazepine core unit was the key step in the synthesis.

Total synthesis of bioactive canthine alkaloid cordatanine comprising in situ double oxidative aromatization of tetrahydrocarbazole - Shelar, S. V.; N. P. Argade (ACS Omega, 2017)
Starting from tryptamine and methoxymaleic anhydride, concise and efficient total synthesis of cordatanine has been accomplished via regioselective reduction of methoxymaleimide, acid-catalyzed intramolecular cyclization of the formed lactamol, in situ stepwise oxidations leading to aromatization, and intramolecular cyclization with the exchange of N-regioselectivity. An attempted synthesis of regioisomeric natural product zanthochilone has been described in brief with reversal of reduction selectivity.

Total synthesis of (+/-)/(+)-subincanadine E and determination of absolute configuration - Kalshetti, Manojkumar G.; N. P. Argade (Journal of Organic Chemistry, 2017)
A facile synthesis of (+/-)-subincanadine E was described from tryptamine-based maleimide. 1,2-Addition of Grignard reagent to maleimide, internal activation of formed lactamol for in situ 1,4-addition of Grignard reagent, and associated position-specific allylic rearrangement in diastereoselective Pictet-Spengler cyclization were the key steps. Enantioselective first total synthesis of naturally occurring cytotoxic (+)-subincanadine E was also accomplished from (S)-acetoxysuccinimide via an unusual syn-addition of cuprate to the alpha/beta-unsaturated lactam. Sinister absolute configuration was assigned to (+)-subincanadine E on the basis of total synthesis. (S)-Acetoxy group in the succinimide precursor was initially employed to impart regio- and stereoselectivity and then as a suitable leaving group to generate the desired conjugated lactam.

Total synthesis of tetrahydroisoquinoline-based bioactive natural products laudanosine, romneine, glaucine, dicentrine, and their unnatural analogues isolaudanosine and isoromneine - Jangir, Ravi; Argade, Narshinha P. (Synthesis-Stuttgart, 2017)
Starting from suitably substituted homophthalic acids, total synthesis of titled alkaloids have been demonstrated in very good yields. The obtained natural products laudanosine and romneine were utilized to accomplish synthesis of two isoquinoline-based alkaloids glaucine and dicentrine. Base-induced selective generation of two different types of benzylic carbanions, their coupling reactions with 3,4-dimethoxybenzyl mesylate, and the regioselective iodination followed by intramolecular aryl-aryl coupling reactions to form the fused biaryl systems were the strategic steps.

Total synthesis of 12, 13-dibenzyl-banistenoside B and analogs - Patil, Suhag S.; Jachak, Gorakhnath R.; Krishna, Gamidi Rama; Argade, Narshinha P.; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2022)
Banistenosides A and B possessing a unique ``azepino(1,2-a)tetrahydro-beta-carboline'' carbon framework were isolated from the stem of Banisteriopsis caapi and showed MAO-A inhibition. Herein, we report the total synthesis of dibenzyl derivative of the untouched natural product in the last two decades, Banistenoside B. The key steps involve construction of 6.5.6.7 tetracyclic core using Pictet-Spengler reaction and intramolecular amide coupling. The stereoselective glycation was achieved through Hotha's protocol using gold catalyst, and silver triflate in the late stage of synthesis. The stereochemistry of most of the essential compounds were confirmed by X-ray crystallography.
Keywords: Au-catalyst; Multiple steps total synthesis; Natural products; Pictet-Spengler reaction; Wittig reaction